Primary inoculum of Venturia inaequalis (Cooke) Wint. in its asexual form in apple – a review - Rancāne, Regīna; Valiuškaitė, Alma; Stensvand, Arne (Frontiers in Horticulture, 2023)
This review summarizes and discusses the geographical distribution, overwintering, dissemination, and management of the asexual stage of Venturia inaequalis, the fungal pathogen causing apple scab. The asexual overwintering of V. inaequalis has primarily been described as wood scab, superficial scab, or bud scab, and more rarely, it is mentioned as overwintering on infected leaves and fruits still attached to the trees. Wood scab is fungal pustules found on new and 1-year-old shoots, but it is also found on 2-year-old wood. It has been reported in many apple-growing countries throughout the world; however, most reports of wood scab being an important source of primary inoculum, as well as the most in-depth studies, are from the UK. Reports from some countries describe what is named superficial scab, which are symptomless infections of the pathogen on shoot surfaces. Overwintering of V. inaequalis on the inner or outer bud scales has also been reported in some countries. Infections may appear as small lesions on the bud scales, but numerous conidia have also been found in buds without symptomatic fungal tissue. The incidence and quantity of overwintering in the asexual stage are dependent on the amount of scab in the previous season, growth characteristics, and cultivar susceptibility. In orchards with limited options for fungicide control and/or in orchards with loss of scab control in the preceding season, conidia of V. inaequalis should not be underestimated as a source of primary inoculum.